How the Germans Are Using the Football Talent Management Program - Mehri Pouyandekia; Zhaleh Memari (Allameh Tabataba'i University Press, 2020)
Purpose: Today, in many developed countries, talent management throughout is the long-term process, under the supervision of expert executive managers and coaches, has been done and is an important concept in football. Therefore, in many developed countries, talented people can come to talent programs and received trained continuously to become professional players. Method: In this study, based on German's football talent management program, and procedure informed by Sandelowski and Barroso's qualitative meta-synthesis. Results: The suggested model has three sections: 1- hardware system, 2- software system, and 3- many subsystems that are collaborating in an executive context. Achievements of this program are not just the detection of talented young players at an early age, but rather a long-term process that is a high-level management program, which, for full success, requires collaboration between many organizations such as the government, football association, footballleagues, clubs, academies, education schools, football schools, coaches, and players. Conclusions: According to results, the growing process of this cycle and its periodic revision show the brilliant future of the German football community in gaining championship and promoting the national identity of Germany over the years. We hope that by studying this system we can introduce it to the researchers and officials in developing countries, who are interested in furthering a developmental view of football.